2018
DOI: 10.56093/ijas.v88i12.85446
|View full text |Cite
|
Sign up to set email alerts
|

Improved ARIMAX modal based on ANN and SVM approaches for forecasting rice yield using weather variables

Abstract: An effort has been made to get precise forecast of rice yield through ARIMAX and proposed hybrid models using weather variables. In this article, two hybrid approaches like ARIMAX-ANN and ARIMAX-SVM have been proposed. Firstly, ARIMAX model was fitted for the considered time series data. Rice yield along with weather variables of Aligarh district of Uttar Pradesh have been considered to evaluate the forecasting performance of the proposed hybrid models. The residuals obtained from the fitted model which exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…The results of the DM test revealed that in two sets (training and testing set) of data, the extreme learning machine intervention model performed better than all other models (Table 8). According to several studies [38][39][40][41][42][43][44] for forecasting time series data in the agricul-tural and related fields, the results showed that AI performed better than the standard ARIMA model, which is in accordance with some previous findings. By considering the MAPE values, a significant difference between the actual and forecasted values can be obtained by the DM test.…”
Section: Discussionsupporting
confidence: 87%
“…The results of the DM test revealed that in two sets (training and testing set) of data, the extreme learning machine intervention model performed better than all other models (Table 8). According to several studies [38][39][40][41][42][43][44] for forecasting time series data in the agricul-tural and related fields, the results showed that AI performed better than the standard ARIMA model, which is in accordance with some previous findings. By considering the MAPE values, a significant difference between the actual and forecasted values can be obtained by the DM test.…”
Section: Discussionsupporting
confidence: 87%
“…For the ARIMAX model, d was set to the default value following the stability test. The influence of p and q on forecast accuracy is discussed later in the section [12]. Results of four groups of cases corresponding to the two case ships are shown in Figure 11.…”
Section: Optimization Of Parametersmentioning
confidence: 99%
“…For multivariate time-series forecasting, the ARIMAX model is a generalization of ARIMA model, which is capable of incorporating an exogenous input variable [12], as shown in Equation (4).…”
Section: Time-series Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to forecast rice yield, Kumar and Kumar (2012) added fuzzy values to the time series [12]. Alam et al (2018) applied two hybrid approaches including ARIMAX-ANN and ARIMAX-SVM for estimating rice yield in India [13]. Jing-feng (2011) used NOAA/AVHRR data to predict rice production in Zhejiang Province through ratio models and regression models [14].…”
Section: Introductionmentioning
confidence: 99%